I was wondering if anyone can tell me how the following identity is derived: Thank you
Follow Math Help Forum on Facebook and Google+
Originally Posted by maggiec I was wondering if anyone can tell me how the following identity is derived: Thank you Start with sin (p+q) - sin (p-q) = sin p cos q+cos p sin q-sin p cos q+cos p sin q = 2 cos p sin q Now let p+q=a ---1 and p-q=b ----2 1+2 2p=a+b implies p=(a+b)/2 1-2 2q=a-b implies q=(a-b)/2 Hence sin p-sin q=2 cos (a+b)/2 sin (a-b)/2
View Tag Cloud